Peripheral neuropathy and gastroenterologic disorders: an overview on an underrecognized association - Spagnoli, Carlotta; Pisani, Francesco; Di Mario, Francesco; Leandro, Gioacchino; Gaiani, Federica; de' Angelis, Gian Luigi; Fusco, Carlo (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Although peripheral neuropathies in children are often of genetic origin, acquired causes should be carefully looked for and ruled out also in the pediatric age. Gastroenterological disorders can be complicated by peripheral neuropathy as a result of micronutrients deficiency, drug toxicity or because of shared pathophysiological mechanisms. Methods: In this descriptive review we sought to give an overview on the most relevant clinical conditions in which peripheral neuropathies are associated with gastro-intestinal disorders or symptoms. Results: We describe the clinical, demographic, and electrophysiological features of peripheral neuropathy in three main clinical scenarios: in the context of common gastroenterological disorders (inflammatory bowel and celiac disease), in the context of micronutrients deficiencies arising from malabsorption irrespective of etiology, and in a rare degenerative mitochondrial disorder, mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) disorder. Conclusions: The association between gastrointestinal and peripheral nervous system symptoms is probably still underrecognized but has to be actively sought, in order to provide prompt diagnosis resulting in optimal care and long-term management with the aim to improve quality of life and, at least in some conditions, try to impact on prognosis.